2008
DOI: 10.21512/tw.v9i1.728
|View full text |Cite
|
Sign up to set email alerts
|

The Accountability of Islamic Microfinance Institution: Evidence from Indonesia

Abstract: The article aims to provide current condition's information on the accountability of Baitul Maal wat Tamwil (BMT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…He concluded that their performances are less than satisfactory as most of the financial assistance is used for consumption purposes. Another interesting study done by Wahyuni (2007) concluded that charity-based organizations in Indonesia do not fall under any regulatory mechanism, lacking any incentives for the managers to have their financial statements audited. Zarka (2007) suggested a monetary waqf (benevolent fund) to overcome the problem of poverty as he divided the poor into two groups-economically active and economically inactive.…”
Section: Islamic Mfismentioning
confidence: 99%
“…He concluded that their performances are less than satisfactory as most of the financial assistance is used for consumption purposes. Another interesting study done by Wahyuni (2007) concluded that charity-based organizations in Indonesia do not fall under any regulatory mechanism, lacking any incentives for the managers to have their financial statements audited. Zarka (2007) suggested a monetary waqf (benevolent fund) to overcome the problem of poverty as he divided the poor into two groups-economically active and economically inactive.…”
Section: Islamic Mfismentioning
confidence: 99%